No colder place - Rozan, S. J. (Rozan, S. J. Lydia Chin/Bill Smith novels., 1997)
When a Manhattan construction site is plagued by an escalating series of thefts and misfortunes, the contractors suspect that they've been targeted by one of their own subcontractors' employees. Brought in to investigate, P.I. Bill Smith goes undercover on the site as a bricklayer - a profession he hasn't practiced for more than twenty-years - to try to uncover the truth about the suspect as well as the troubles on the job site. With his sometime-partner, Chinese-American P.I. Lydia Chin, working as his inside contact, Smith finds himself in the midst of a much more serious case - a case that has escalated from fraud to murder, one that could reach through layers of corruption into the very depths of the underworld.